Performance Comparison of AODV and AOMDV Protocol Routing with TCP and UDP on Mobile Ad-Hoc Network (Manet) Using Malicious Node (Blackhole Attack) - Faizah, Nurul; Masruroh, Siti Ummi; Armenia, Ivan Gustra Manca (MULTINETICS, 2019)
Transmission package delivery can be a problem of routes on the network, one of them is the Wireless network. Mobile Ad-Hoc Network (MANET) topology is often used on Wireless networks. The existence of a malicious node is a threat to MANET. Package delivery uses AODV and AOMDV Protocol Routing in TCP and UDP packet transmission. This study uses a simulation method using NS2, NAM and AWK. The Quality of Service (QoS) parameters used are throughput, packet loss, and jitter. Simulations are carried out using malicious nodes, the results on the AOMDV TCP graph have the highest input values and the best packets but are difficult to minimize energy, while for the TCP jitter values graph is best because it has a flow control function that can adjust the trajectory. The results in AOMDV TCP have the highest input value and the best packet loss but it is difficult to minimize energy, while for TCP value jitters it is best because it has a flow control function that can adjust the trajectory